2023
DOI: 10.1155/2023/1154808
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Modules and Key Pathways Associated with Innervation in Graft Bone—CGRP Regulates the Differentiation of Bone Marrow Mesenchymal Stem Cells via p38 MAPK and Wnt6/β-Catenin

Abstract: Bone resorption occurs after bone grafting, however, contemporaneous reconstruction of the innervation of the bone graft is a potential treatment to maintain the bone mass of the graft. The innervation of bone is an emerging research topic. To understand the potential molecular mechanisms of bone innervation after bone grafting, we collected normal iliac bone tissue as well as bone grafts with or without innervation from nine patients 1 year after surgery and performed RNA sequencing. We identified differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…129 Under homeostatic circumstances, CGRP administration can promote BMSCs migration and differentiation, increasing new bone formation with the involvement of the Wnt/β-catenin pathway, 127,130 as well as promoting innervation and osteogenesis in graft bone. 131 Blocking the CGRP receptor resulted in a reduction of bone mass and other parameters associated with bone formation, while bone resorption was not affected. 132 It is further concluded that the isoform CGRPα takes part in the activation of periosteal mineralizing surfaces under mechanical loading.…”
Section: Cgrpmentioning
confidence: 98%
“…129 Under homeostatic circumstances, CGRP administration can promote BMSCs migration and differentiation, increasing new bone formation with the involvement of the Wnt/β-catenin pathway, 127,130 as well as promoting innervation and osteogenesis in graft bone. 131 Blocking the CGRP receptor resulted in a reduction of bone mass and other parameters associated with bone formation, while bone resorption was not affected. 132 It is further concluded that the isoform CGRPα takes part in the activation of periosteal mineralizing surfaces under mechanical loading.…”
Section: Cgrpmentioning
confidence: 98%
“…The exploration of various potential transformation strategies between neural and bone tissues has emerged as a key focus in the development of tissueengineered bone [20]. Innervation is acknowledged to play a crucial regulatory role in bone formation, and current research is intensifying its focus on the utilization of nerve bundles or bone implant materials in bone engineering applications [21].Innervation in bone functions primarily through neural-related bioactive factors (including recombinant growth factors, neuropeptides, hormones, and non-coding RNAs), and our previous studies have demonstrated the role of the neurotransmitter CGRP regulates the differentiation of bone marrow mesenchymal stem cells via p38 MAPK and Wnt6/β-Catenin in bone homeostasis [22]. However, we still need a more comprehensive understanding of the speci c role of neural innervation in the molecular mechanisms of bone tissue metabolism, especially in research involving non-coding RNA related mechanisms.…”
Section: Introductionmentioning
confidence: 99%